PERILAKU KONSUMEN FROZEN READY-MADE MEALS DAN STRATEGI PEMASARAN PADA DEWASA AWAL DI INDONESIA - Fachruddin, Ismi Irfiyanti; Syamsuriah, Syamsuriah (JOURNAL HEALTH AND NUTRITIONS, 2025)
Frozen ready-made meals have become a significant part of modern diets, particularly among Millennials and Generation Z. This shift, driven by urbanization and convenience, aligns with global food consumption trends and poses implications for health, sustainability, and marketing strategies. This study aims to explore the consumption patterns, attitudes, and marketing touchpoints of frozen ready-made meal consumers in Indonesia, focusing on Millennials and Generation Z. It also seeks to identify effective strategies for businesses to engage with this demographic. A structured survey was conducted with 249 respondents representing consumers of frozen ready-made meals in Indonesia. The data covered demographics, media consumption, advertising exposure, and attitudes toward health and sustainability. Comparative analysis was performed to identify trends and patterns in their behavior. The results show a strong reliance on digital platforms, with 94% engaging with digital video content and 80% exposed to video advertising. Smartphones dominate as the primary device for media consumption (98%), and social media usage is high. Health-conscious behaviors are prevalent, with 76% actively trying to eat healthily, though only 25% aim to reduce meat consumption, reflecting limited engagement in sustainable dietary habits. Economic stability, education, and environmental issues are among the top societal concerns. The study highlights the need for businesses to leverage digital platforms, particularly video advertising and social media, to effectively reach Millennials and Generation Z. Emphasizing health-conscious and sustainable options can resonate with their values. A balanced approach, integrating digital innovation with traditional advertising methods, is essential for fostering stronger connections and ensuring long-term consumer loyalty in this demographic.